Effects of heat-treatment on permeability of untreated and nanosilver-impregnated native hardwoods - Reza Taghiyari, Hamid (Maderas. Ciencia y Tecnología, 2025)
The effects of heat-treatment on permeability are the main topic of the present study. Longitudinal dowel shape pairs of specimens were prepared from three native species and their specific gas permeability values were measured. From each pair, one specimen was kept for heat-treatment and the other was impregnated with 200 ppm nano-silver suspension; the size range of nanoparticles was 20-80 nm. In six consecutive steps, each pair was heated at 50, 75, 100, 125, 150, and 185°C. Results showed that gas permeability increased when specimens were heated at 50°C as a result of the loss of bond-water and consequent shrinkage. Permeability sharply decreased when the specimens were heated at 75°C and gradually increased at each step up-to 150°C. At 185°C, permeability again decreased in. The sharp decrease in permeability at 75°C was possibly due to irreversible hydrogen bonding in the course of water movements within the vessel perforations and pore system of cell walls. The gradual increase in permeability at higher temperatures, though, might be due to higher internal stresses that are released as micro-cracks develop, thus leading to a greater capability of fluidtransfer. Nano-silver impregnation intensified this process.